Continuance Intention Factors of Mobile Payment Services Provided by OVO - Nico Septian Pranoto; Edwin Edwin (iBuss Management, 2019)
Indonesia financial industry’s growth is supported by technology especially by the growth of electronic payments. The trend of electronic payments can be seen from mobile payment which is the main focus of this research. Therefore, this research focuses on mobile payment and OVO as the research object. The researchers emphasize on the post-adoption with the continuance intention as the research focus. As suggested by past researchers, the influencing factors used in this research are system quality, information quality, service quality and price promotion where it is influenced through trust, flow and satisfaction. In this research, 455 samples are collected using simple random sampling and 403 samples are analyzed using Structural Equation Modelling. The result implies that system quality and information quality have significant positive impact toward trust and flow. System quality does not have significant impact toward satisfaction. Information quality has significant negative impact toward satisfaction. Service quality has significant positive impact toward trust but significant negative impact toward flow and satisfaction. Price promotion has a significant positive impact towards satisfaction. Trust has a significant positive impact towards flow and flow has a positive impact towards satisfaction. Lastly, trust, flow and satisfaction have a significant impact towards continuance intention. Keyword: Continuance Intention, Mobile Payment, Structural Equation Modelling, Exogenous Variables, Endogenous Variables.